OUTBREAK LEPTOSPIROSIS DENGAN VEKTOR TIKUS PADA DAERAH RAWAN BANJIR DI SURABAYA - Freshinta Jellia Wibisono; Sheila Marty Yanestria (JURNAL KAJIAN VETERINER, 2019)
Surabaya was the second largest city in Indonesia and also a city that had the flood-prone areas. Flooding that occurred caused some cases of the disease, one of the disease is leptospirosis. Leptospirosis was an acute infectious disease caused by the harmful bacteria Leptospira and rats were the main reservoir. Flooding were transmission medium of Leptospira derived from rat urine. This case study was an observational descriptive study using case control study design to describe the incidence of leptospirosis in terms of the presence of disease agents Leptospira sp in rat vector in Surabaya flood-prone areas Surabaya. Data of rats infected in flood prone areas obtained from the results of rapid test Lepto Tek Lateral Flow to identify the presence of Leptospira in serum of rats. Data of the presence of Leptospira in rats and flood-prone are were analyzed descriptively. Results showed 100% negative Leptospira Sp. on samples of blood serum with an examination of Leptotek Lateral Flow in flood prone areas in Surabaya showed that during the study started in May 2016 to October 2016 there were no mice infected with the bacterium Leptospira sp. in flood prone areas Wonokromo, Bendul Merisi, Kupang Krajan and Sidomulyo.